Value-Added Assessment in Practice Lessons from the Pennsylvania Value-Added Assessment System Pilot Project - McCaffrey, Daniel F. (RAND Corporation, 2007)
Value-added assessment (VAA) systems use statistical techniques to analyze test-score data; VAA data is intended to help educators make more informed decisions about curriculum and instruction. The authors examined the rollout of Pennsylvania's VAA program, and found that, in its pilot phase, the program had little effect on student achievement and received limited use by most principals and teachers at schools participating in the program.